Mothers, fathers and educators' beliefs about play in Chilean preschool children. Issue 2 (3rd April 2022) - Aldoney, Daniela; Coo, Soledad; Mira, Andrea; Valdivia, Josefina
ABSTRACT: Robust data exist on the relation between play and children's positive development. Yet, the time children devote to play has decreased in the last decades. Guided by the premise that adults' beliefs about play are related to the way in which adults promote it, we asked 380 mothers, 89 fathers, and 83 early childhood educators in Santiago, Chile, about their beliefs about play and its relation to academic learning. Results showed similarities and differences in the value given to free and structured play and electronic activities by the three groups of participants. Participants differed in the academic value of play by socioeconomic status but agreed on the value of play in children's academic skills. Fathers valued electronic activities more than mothers and early childhood educators. Data from this study may inform interventions and curriculum to foster play as an essential tool for child development in Chile.